Sharp-Wave Ripple Frequency and Interictal Epileptic Discharges Increase in Tandem During Thermal Induction of Seizures in a Mouse Model of Genetic Epilepsy - Cheah, Christine S.; Beckman, Megan A.; Catterall, William A.; Oakley, John C. (Frontiers in Cellular Neuroscience, 2021)
Dravet Syndrome (DS) is a genetic, infantile-onset epilepsy including refractory seizures and severe cognitive impairment. While network level pathophysiology is poorly understood, work in genetic mouse models of DS reveals selective reduction of inhibitory interneuron excitability, a likely mechanism of seizures and comorbidities. Consistent with the critical role of interneurons in timing and recruitment of network activity, hippocampal sharp wave ripples (SPW-R) – interneuron dependent compound brain rhythms essential for spatial learning and memory - are less frequent and ripple frequency is slower in DS mice, both likely to impair cognitive performance. Febrile seizures are characteristic of DS, reflecting a temperature-dependent shift in excitation-inhibition balance. DS interneurons are sensitive to depolarization block and may fall silent with increased excitation precipitating epileptic transformation of ripples. To determine the temperature dependence of SWP-R features and relationship of SPW-R to hippocampal interictal activity, we recorded hippocampal local field potentials in a DS mouse model and wildtype littermate controls while increasing core body temperature. In both genotypes, temperature elevation speeds ripple frequency, although DS ripples remain consistently slower. The rate of SPW-R also increases in both genotypes but subsequently falls in DS mice as interictal epileptic activity simultaneously increases preceding a thermally-evoked seizure. Epileptic events occur intermixed with SPW-R, some during SPW-R burst complexes, and transiently suppress SPW-R occurrence suggesting shared network elements. Together these data demonstrate a temperature dependence of SPW-R rate and ripple frequency and suggest a pathophysiologic mechanism by which elevated temperature transforms a normal brain rhythm into epileptic event.